Biothermodynamics. - Johnson, Michael L., 1947-; Holt, Jo M.; Ackers, Gary K. (Methods in enzymology, 2011)
The use of thermodynamics in biological research can be equated to an energy book-keeping system. While the structure and function of a molecule is important, it is equally important to know what drives the energy force. This volume presents sophisticated methods for estimating the thermodynamic parameters of specific protein-protein, protein-DNA and small molecule interactions. Elucidates the relationships between structure and energetics and their applications to molecular design, aiding researchers in the design of medically important molecules.